2022
DOI: 10.1038/s41392-022-01033-8
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein ZCCHC4 promotes human cancer chemoresistance by disrupting DNA-damage-induced apoptosis

Abstract: RNA-binding proteins (RBPs) play important roles in cancer development and treatment. However, the tumor-promoting RBPs and their partners, which may potentially serve as the cancer therapeutic targets, need to be further identified. Here, we report that zinc finger CCHC domain-containing protein 4 (ZCCHC4) is of aberrantly high expression in multiple human cancer tissues and is associated with poor prognosis and chemoresistance in patients of hepatocellular carcinoma (HCC), pancreatic cancer and colon cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 52 publications
(59 reference statements)
0
23
0
Order By: Relevance
“…In vitro and in vivo experiments have shown that ZCCHC4 enhances the chemotherapy resistance in HCC cells against DNA-damaging agents. Moreover, its interaction with the lncRNA AL133467.2 impedes apoptosis induced by DNA damage [ 87 ]. NSUN2, an m5C RNA methyltransferase, participates in the regulation of cell proliferation and metastasis and is upregulated in various tumors [ 42 ].…”
Section: Biological Function Of Methylation Modification In Ncrnas In...mentioning
confidence: 99%
“…In vitro and in vivo experiments have shown that ZCCHC4 enhances the chemotherapy resistance in HCC cells against DNA-damaging agents. Moreover, its interaction with the lncRNA AL133467.2 impedes apoptosis induced by DNA damage [ 87 ]. NSUN2, an m5C RNA methyltransferase, participates in the regulation of cell proliferation and metastasis and is upregulated in various tumors [ 42 ].…”
Section: Biological Function Of Methylation Modification In Ncrnas In...mentioning
confidence: 99%
“…ZCCHC4 could specifically promote proliferation of HCC cells in vitro and in vivo, partially dependent on catalyzing rRNA methylation and promoting optimal global translation. 42,43 Furthermore, ribosome-associated mRNA sequencing studies have revealed that ablation of ZCCHC4 caused a strong reduction of m6A in total rRNA. The loss of m6A modification of 28 S rRNA disrupts the stringent control of translation on mRNA populations, leading to altered optimal activity of ribosomes as indicated by codon-specific translation defects and deviating translation activity.…”
Section: The M6a Modification At 28 S Rrna Affects Ribosome Functionmentioning
confidence: 99%
“…Interestingly, ZCCHC4 protein is overexpressed in tumor tissues of hepatocellular carcinoma (HCC), accompanied by increased m6A levels in 28 S rRNA. ZCCHC4 could specifically promote proliferation of HCC cells in vitro and in vivo, partially dependent on catalyzing rRNA methylation and promoting optimal global translation 42,43 . Furthermore, ribosome‐associated mRNA sequencing studies have revealed that ablation of ZCCHC4 caused a strong reduction of m6A in total rRNA.…”
Section: The M6a Modification At 28 S Rrna Affects Ribosome Functionmentioning
confidence: 99%
“…Taking advantage of oligonucleotides binding to the AR N-terminal domain or AR RNA motif to block the interaction between SLNCR and AR represents a feasible therapeutic strategy in the process of melanoma ( 136 ). In addition, lncRNA-ZCCHC4 inhibits DNA damage-induced apoptosis by interacting with lncRNA-AL133467.2, and knockdown of this gene can enhance chemosensitivity to DDA in hepatocellular carcinoma cells, which is a potential target to improve the chemotherapeutic effect ( 137 ). Additionally, the lncRNA-POU3F3 expression level was elevated in dacarbazine-resistant melanoma cells, and knockdown of POU3F3 restored the sensitivity of cells to dacarbazine by secreting miR-650 and upregulating the expression of MGMT protein ( 138 ).…”
Section: Lncrnas As Potential Therapeutic Targetsmentioning
confidence: 99%